Fatal chloroquine intoxication - Keller, Thomas; Schneider, Andrea; Lamprecht, Robert; Aderjan, Rolf; Tutsch-Bauer, Edith; Kisser, Wolfgang (Forensic science international, 1998)
A suicidal ingestion of an unknown quantity of Resochin® (chloroquine) tablets is described. Although chloroquine is known since 1934, intoxications due to chloroquine overdose are rather rare in European countries. The authors report on a new and fast method of analysing and determining the chloroquine concentration in body fluids and postmortem specimens. The analytes were extracted from alkalinized samples into ethyl acetate before GC/MS analysis. The analyses of chloroquine were performed without any complex sample clean-up steps and, in addition, with little sample material. The proposed method resulted in a rapid procedure most useful in cases of deliberate poisoning with the anti-inflammatory and antimalarial drug chloroquine.